Impact of Online Music Competitions on the Young Musicians’ Professional Skills and Their Musical Development During the Covid-19 Pandemic - Tokay, Dilbağ (European Journal of Social Science Education and Research, 2023)
Classical music competitions present a medium for the development and motivation of young musicians. In this context, they prepare young musicians to professional life and play an important role in their career. Online competitions became more popular due to the Covid-19 pandemic with an increasing number of high professional quality applicants. This research aims to focus on the impact of online music competitions on the young musicians’ professional skills and their musical development. The research will set forth the differences between online competitions and real life competitions from various aspects such as application process, video presentations, and efficiency of the young musicians in using available technology, jury formation, evaluation of the applicants’ performances by the jury as well as the applicants’ evaluation of their own performance among other applicants.